Evaluating the resource allocation efficiency of the healthcare system in Taiwan. (31st October 2008) - Wu, Chia-Hsuan; Chang, Ching-Cheng; Kuo, Ken N.
In this study, we introduced the concept of the integrated healthcare system into budget allocation decisions and analysed the potential improvement in healthcare performance by reallocating the budget among the preventive care, medical care and long-term care services. We have applied an extended version of the Data Envelopment Analysis (DEA) approach to evaluate the efficiency and performance of the healthcare system in 23 counties and cities in Taiwan for the year 2003. The results indicated that the efficiency in each city and county's healthcare system varied with local conditions. With reallocation of their healthcare budgets, we observed a gain in efficiency in healthcare of the cities and counties studied. The general recommendations for budget reallocations are along the lines of increasing the amount invested in preventive and long-term care while reducing expenditures on medical care.